Use of ergonomic principles in manual order picking systems - Labus, Nina (Logistics and sustainable transport, 2018)
Successful companies are continually striving to streamline costs and optimize processes, enabling them to grow progress, develop and ensure competitiveness on the market. A large part of the costs arises in warehouses, where up to 55% of total costs are generated by order- picking, which makes it important and interesting in terms of research. The paper explores "picker to part" order- picking concept, which enables flexible work and is the optimal choice for most companies. The concept is associated with a high level of work- related injuries and work -related illnesses. Work requires physical efforts resulting from handling heavy goods, performing repetitive movements and using manipulative means. Hum an as the main actor of the concept affects the costs caused by picking and the quality of work done, which depends on technological support, physically and psychologically capable and motivated people. Due to the high costs of service, the focus on time planning and productivity increases. Contrary, the lack of attention is paid to the working conditions and the health status of the pickers. To overcome this gab, a review of scientific and professional literature on ergonomic principles in picking concept "picker to part" was carried out, followed by a quantitative survey of ergonomic properties in warehousing activities. Results revealed that more than 60% of the surveyed order-pickers associate problems with health with the characteristics of work, about 24% of them associate health problems with the use of a particular means of transport, and all agree that provided measures to reduce physical effort and greater support of technologies influence on increased speed of work and better health status of order-pickers.
Keywords: costs; ergonomics; injuries; picker- to -part; picking; productivity